BUILDING FOOD SECURITY AT MSMEs IN INDONESIA THROUGH NATIONAL AND REGIONAL FACILITATORS - I Made Indra P; Robidi Robidi; Wahyuari Wahyuari; Agus Subrata (International Journal of Engagement and Empowerment, 2022)
Food safety is an essential aspect of sanitation science. Food safety is a condition and an effort to prevent food from being contaminated by biological, chemical, and other objects that disturb, harm, and endanger human health. For the community, safe food is food that is clean, safe, and does not cause disease. Many of our environments are directly or indirectly related to the human food supply. Food preservation methods, including salting, adding sugar, smoking, and more, have been practiced since human existence. This work in the community is done by national and regional facilitators who train and assist STMA Trisakti, KOPITU, and BPOM. From the 5th of November until the 5th of December 2021, participants will receive instruction and guidance. The outcomes of the activities have a positive impact. The data before the activity evidence the significant increase in MSME knowledge about food safety. The number of knowledges in the excellent category of 5 participants increased to 17 participants after the activity, and the satisfactory category before the activity was 10 participants, and after the activity became 50 participants